Right renal lithiasis in ectopic kidney that simulates acute appendicitis - Mendieta-Madiedo, María Camila; Montes Arcón, Pablo Salomón; Martínez Otero, María Camila (Cirugía del Uruguay, 2024)
A 45-year-old male patient presented with a 12-hour history of clinical symptoms characterized by abdominal pain, in the flank and right iliac fossa, associated with vomiting of a bilious appearance.